Perbedaan Indeks Massa Tubuh Pada Akseptor KB Suntik Cyclofem dan Depo Medroksi Progesteron Acetat (DMPA) Dengan Jangka Waktu Penggunaan Lebih Dari 1 Tahun - Linda Juwita; Ninda Ayu Prabasari; Anggi Siska Mega Selvia (JURNAL NERS LENTERA, 2021)
Users of injectable hormonal contraceptives experience weight gain which has an impact on BMI. The purpose of this study was to determine the difference in body mass index between cyclofem injection contraceptive acceptors and Depo Medroxy Progesterone Acetate (DMPA) with a period of use of more than 1 year. The research method in this study was cross-sectional. The variable in this study is BMI. The population in this study were women of childbearing age who used cyclofem injectable hormonal contraception and Active DMPA for more than 1 year of use in the independent practice of midwives, totaling 120 people. The sampling technique used is purposive sampling. Samples that meet the inclusion and exclusion criteria are 64 respondents. Based on the table above, the majority of respondents who used 1-month injections were 16 respondents, and 14 respondents used 3-month injections. After the normality test, the results obtained asymp. Sig. (2-tailed) 0.732 > 0.05 which means that the data in this study are normally distributed so that the statistical test carried out is an independent t-test with a result of 0.891 > 0.05 and it means that there is no difference in body mass index between cyclofem injection contraceptive acceptors and depo medroxy Progesterone acetate (DMPA) with a duration of use of more than 1 year. Factors that cause normal BMI of injection contraceptive users are insignificant weight gain and physical activity.